Interaction of the new inhibitor paxlovid (PF-07321332) and ivermectin with the monomer of the main protease SARS-CoV-2: A volumetric study based on molecular dynamics, elastic networks, classical thermodynamics and SPT. (August 2022) - Alvarado, Ysaias José; Olivarez, Yosmari; Lossada, Carla; Vera-Villalobos, Joan; Paz, José Luis; Vera, Eddy; Loroño, Marcos; Vivas, Alejandro; Torres, Fernando Javier; Jeffreys, Laura N.; Hurtado-León, María Laura; González-Paz, Lenin
Abstract: The COVID-19 pandemic has accelerated the study of drugs, most notably ivermectin and more recently Paxlovid (PF-07321332) which is in phase III clinical trials with experimental data showing covalent binding to the viral protease M pro . Theoretical developments of catalytic site-directed docking support thermodynamically feasible non-covalent binding to M pro . Here we show that Paxlovid binds non-covalently at regions other than the catalytic sites with energies stronger than reported and at the same binding site as the ivermectin B1a homologue, all through theoretical methodologies, including blind docking. We volumetrically characterize the non-covalent interaction of the ivermectin homologues (avermectins B1a and B1b) and Paxlovid with the mM pro monomer, through molecular dynamics and scaled particle theory (SPT). Using the fluctuation-dissipation theorem (FDT), we estimated the electric dipole moment fluctuations at the surface of each of complex involved in this study, with similar trends to that observed in the interaction volume. Using fluctuations of the intrinsic volume and the number of flexible fragments of proteins using anisotropic and Gaussian elastic networks (ANM+GNM) suggests the complexes with ivermectin are more dynamic and flexible than the unbound monomer. In contrast, the binding of Paxlovid to mM pro shows that the mM pro -PF complex is the least structurally dynamic of all the species measured in this investigation. The results support a differential molecular mechanism of the ivermectin and PF homologues in the mM pro monomer. Finally, the results showed that Paxlovid despite beingbound in different sites through covalent or non-covalent forms behaves similarly in terms of its structural flexibility and volumetric behaviour. Graphical Abstract: ga1 Highlights: The mechanism of formation of the non-covalent complex of ivermectin-M pro and Paxlovid-M pro depends on the binding site. Ivermectin-B1a and Paxlovid can bind to M pro and affect monomer conformation, hydration, and flexibility in a similar way. Ivermectin-B1a and Paxlovid could affect the dimerization reaction of the monomer to form M pro protease by similar mechanism. Ivermectin-B1b could affect the dimerization reaction of M pro by a different mechanism than ivermectin-B1a and Paxlovid. Paxlovid forms covalent and non-covalent complexes with the M pro monomer with similar volume behavior and deformability.